The abundance and diversity patterns of seaweed communities on natural and artificial substrata at Sodwana Bay, South Africa - Gersun, Leanne (University of Cape Town, 2015)
Includes bibliographical references. === The high latitude coral communities of southern Africa suffered minimal impacts during mass bleaching events in the recent past. However, during the 2005 warm-water anomaly in the southern Indian Ocean, coral bleaching reached unprecedented levels. There is surprisingly little known about the fate of bleached corals, which may either regain their zooxanthellae and recover, or may die, in which case they generally become overgrown by macroalgae. The nature and dynamics of this algal overgrowth are not well understood. This study was done on Two-Mile Reef, Sodwana Bay, located in the iSimangaliso Wetland Park, a World Heritage Site. The first aim was to investigate the abundance and diversity of benthic algal communities colonising different hard substrata (comprising bleached digitate, brain and plate coral assemblages, and beach rock). The second was to compare the algal communities colonising various artificial hard substrata. The third was to document the species of non-geniculate coralline red algae found on the natural hard substrata during sampling. Fieldwork was carried out during the marine autumn (March) and spring (September) of 2010 using SCUBA. A total of 90 quadrats (10 cm x 10 cm) were sampled and the underlying substratum was recorded and classified. A Braun-Blanquet scale was used to assign cover-abundance values to each species within each quadrat. Additionally, the relative cover of different types of substrata was estimated using line-point intercept methods. Multivariate analysis (detrended correspondence analysis) and cluster analysis (complete linkage Bray-Curtis) were used to show how substrata and season relate with respect to their seaweed flora. Additionally, Kruskal-Wallis nonparametric tests with pairwise Mann-WhitneyU-tests were used to examine differences in macroalgal assemblages among substratum types.